A Study On The Histopathological Analysis Of Nasal Masses Among Patients Attending The Ent Department Of Pakistan Institute Of Medical Sciences, Islamabad - Malik Jawad Faisal; Muhammad Arshad; Moniba Zafar; Ahmed Hasan Ashfaq; Syed Fahd Shah (Journal of Rawalpindi Medical College)
Objective: The study was conducted to understand the different histopathological patterns, the classification of nasal tumours, and the relative distribution of the various lesions by age and sex.